2018
DOI: 10.1002/trtr.1692
|View full text |Cite
|
Sign up to set email alerts
|

Coaching in Practice‐Based Literacy Education Courses

Abstract: As teacher education programs shift to more practice‐based methods in the preparation of literacy teachers, the ways in which teacher educators support the learning of their preservice teachers (PSTs) becomes paramount. In an effort to support PSTs in developing competency in instructional literacy routines, coaching has been found to support PSTs’ understandings of how to teach for student learning. In this article, three approaches to coaching are explored: rehearsals, a modified behind‐the‐glass approach, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The precise roles of literacy teacher educators and classroom teachers during field experiences were not clear (Lenski & Nierstheimer, 2006), nor were the ways in which preservice teachers were prepared to conduct effective classroom observations (Young & Bender-Slack, 2011). Additionally, no information was given that described how mentors supported preservice teachers' professional growth with coaching strategies (Husbye et al, 2018), demonstrations of teaching techniques (Linek et al, 1999), debriefing discussions (Harlin, 1999), or the provision of feedback (Fang & Ashley, 2004). Moreover, many reported field experiences did not appear to be closely aligned with literacy teacher preparation coursework, thereby signaling a disconnection between university-and fieldbased learning experiences (Zeichner, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise roles of literacy teacher educators and classroom teachers during field experiences were not clear (Lenski & Nierstheimer, 2006), nor were the ways in which preservice teachers were prepared to conduct effective classroom observations (Young & Bender-Slack, 2011). Additionally, no information was given that described how mentors supported preservice teachers' professional growth with coaching strategies (Husbye et al, 2018), demonstrations of teaching techniques (Linek et al, 1999), debriefing discussions (Harlin, 1999), or the provision of feedback (Fang & Ashley, 2004). Moreover, many reported field experiences did not appear to be closely aligned with literacy teacher preparation coursework, thereby signaling a disconnection between university-and fieldbased learning experiences (Zeichner, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mentors support preservice teachers with guided and supervised field experiences by demonstrating and modeling explicit teaching techniques (Linek et al, 1999), holding debriefing discussions (Harlin, 1999), and providing timely and helpful feedback (Fang & Ashley, 2004). Mentors also employ a repertoire of coaching strategies to preserve the complexities of teaching, promote ethical and professional decision-making, and keep teaching attainable among preservice teachers (Husbye, Wessel Powell, Vander Zanden, & Karalis, 2018).…”
Section: Overview Of Field Experiencesmentioning
confidence: 99%
“…Research on coaching has shown to be beneficial for those on the receiving end when coaching methods are applied in a constructive manner that promotes positive reinforcement of effective practice while encouraging corrective practice with low affectivity. Coaching during teaching-learning rehearsals provides TCs structured support as they learn to translate theory into practice (Husbye et al, 2018). When supported by coaching and feedback from experienced practitioners, TCs become more aware of their pedagogical strengths and weaknesses (Stahl et al, 2016;Won et al, 2019;Bukko and Liu, 2021).…”
Section: Instructional Coachingmentioning
confidence: 99%
“…One such approximation of practice is the rehearsal, "a social setting for building novices' commitment to teach ambitiously" (Lampert et al, 2013, p. 227). During a rehearsal, the teacher educator supports the PST by guiding them through potential lines of thought, including the alignment of content knowledge (Husbye et al, 2018) as well as the articulation of the instructional routine itself (Husbye, 2018) in anticipation of enacting a lesson plan with students. While a teacher educator might utilize any of a wide range of potential approximations (see Schutz et al, 2018), I utilized rehearsals within my literacy coursework to support PSTs in preparing to teach small groups of 2nd-grade students in focused literacy instruction.…”
Section: Play In Teacher Educationmentioning
confidence: 99%